Shrimarti Rukmini Devy - Qonita Rachmah; Riris Diana Rachmayanti; Thini Nurul Rochmah; Shrimarti Rukmini Devy; Sri Andari; Ismayani; Wuri Diah Handayani; Ratu Dien Prima Fermeza; Rufaida Adya Nur Avianti Ulya (Universitas Airlangga, 2023)
Background: Indonesia is targeting to reduce stunting by 14% in 2024. Behavior change communication is one of the 5 (five) pillars of national stunting prevention. Previous research explained that the Interpersonal Communication (KAP) approach succeeded in modify behavior changes to reduce the incidence of stunting. Objectives: This study aims to analyze the efficacy of Interpersonal Communication (KAP) training on the knowledge of Puskesmas health workers to change community behavior related to stunting. Methods: This study used a quasi-experimental design with one pre-posttest group. Total samples were purposively selected, 168 nutritionists and midwives at the health center in the work area of the Sidoarjo District Health Office. The effectiveness of KAP training was assessed by the KAP knowledge indicator using 20 multiple choice questions questionnaire. The questionnaire was filled out twice. KAP training is handled by 4 (four) trained health workers from the Ministry of Health for 6 hours/ day for 2 days. Paired t-test statistical test was used to see the significant changes in knowledge. Results: Based on the results of the analysis, there was a significant increase in both the total correct answers and knowledge scores at KAP training (p<0.000). Conclusions: The efficacy of KAP training showed that similar programs can be implemented with broader targets such as cadres, PKK, religion leaders, and society leaders.